Behind the Scenes: The Impact of Bioactive Phenylpropanoids on the Growth Phenotypes of Arabidopsis Lignin Mutants - El Houari, Ilias; Boerjan, Wout; Vanholme, Bartel (Frontiers in Plant Science, 2021)
The phenylpropanoid pathway converts the aromatic amino acid phenylalanine in a wide range of secondary metabolites. Most of the carbon entering the pathway incorporates in the building blocks of lignin, an aromatic polymer providing mechanical strength to plants. Carbon skeletons not used for lignin leave the pathway to distinct classes of metabolites via intermediates that serve as branch-points from the core pathway. Untangling this metabolic network in Arabidopsis was largely done using phenylpropanoid pathway mutants, all with different degrees of lignin depletion and associated growth defects. The phenotypic defects of some phenylpropanoid pathway mutants have been attributed to differentially accumulating phenylpropanoids or phenylpropanoid-derived compounds. Here, we discuss the role of these bioactive compounds as causal factors of the growth defects of lignin mutants in Arabidopsis.